Hubungan Self Efficacy dan Motivasi dengan Aktivitas Fisik pada Pasien Diabetes Melitus Tipe 2 - Cinta Mirta Putri Oktaviani; Dwi Yogo Budi Prabowo; Hanifah Sahar Al Afra (Institut Nalanda, 2026)
Type 2 diabetes mellitus is a condition in which the body cannot effectively use available insulin or the pancreas does not produce sufficient insulin. Factors such as physical activity, motivation, and self-efficacy influence patients’ ability to perform diabetes self-management. This quantitative study determined the correlation between self-efficacy, motivation, and physical activity among patients with Type 2 Diabetes Mellitus by employing a cross-sectional design. A total of 91 respondents were selected through purposive sampling. The resarchers used the Diabetes Management Self-Efficacy Scale (DMSES) to measure self-efficacy, the Treatment Self-Regulation Questionnaire (TSRQ) to assess motivation, and the International Physical Activity Questionnaire (IPAQ) to evaluate physical activity. The result showed that most respondents had high self-efficacy (71.4%), poor motivation (58.2%), and moderate levels of physical activity (7.4%). Spearman’s Rank test reveales a significant positive correlation between self-efficacy and physical activity (p = 0.043; r = 0.213), indicating that higher self-efficacy was associated with higher levels of physical activity, although the strength of the relationship was weak. In contrast, motivation was not significantly associated with physical activity (p = 0.214). Future researchers should consider using different research approaches to provide a clearer understanding of factors that may influence physical activity, such an age, daily routines, family support, and physical condition.